Community gardens as commons through the lens of the diverse economies framework: A case study of Austin, TX. (May 2023) - Ponstingel, Daria
Abstract: Community gardening involves physical transformation of land, which then promotes community-identity formation and the production of place. This is a case study of community gardens in Austin, Texas (USA) as different types of commons with a focus on the Diverse Economies framework's principles of the successful governance and management. This paper argues that community gardens represent biophysical, cultural, social, and knowledge commons, therefore, their success depends on the social value they provide in addition to their physical yield. This qualitative research uses key-informant interviews with community gardens' representatives to draw evidence that: 1) community gardens represent different types of commons and 2) the governance approaches and management of community gardens include the principles of 'ethical action' described by the Diverse Economies framework. This analysis shows that 18 out of 26 community gardens in Austin follow all six principles of ethical action, and the degree of use of these principles depends on the garden's purposes and values, socioeconomic profile of its members, and its management structure. The results also shows that community gardens in Austin appear to be less aware or less concern with the ecological services related to gardening. Highlights: Biophysical, cultural, social, and knowledge commons are present in community gardens. The success of community gardens depends on both social value and the physical yield. The Diverse Economies framework proposes principles of successful governance. 18 out of 26 community gardens in Austin follow all six principles of ethical action. Garden's goals, attributes and management structure affect the use of these principles.